2020
DOI: 10.3389/fonc.2020.578756
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase III Study of Abemaciclib Versus Erlotinib in Patients with Stage IV Non-small Cell Lung Cancer With a Detectable KRAS Mutation Who Failed Prior Platinum-Based Therapy: JUNIPER

Abstract: with erlotinib (HR = 0.583 [95% CI: 0.470, 0.723]; p <.000001). ORR was 8.9% and 2.7% (p = .010), and the disease control rate was 54.4% and 31.7% (p <.001) with abemaciclib and erlotinib, respectively. Safety results reflected the known safety profiles of abemaciclib and erlotinib. Conclusions: In this study, the primary endpoint of OS was not met; PFS and ORR were improved with manageable toxicity in the abemaciclib arm. The increases in response rates and PFS support further investigation of abemaciclib in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…The most promising results were seen in breast cancer and non-small cell lung cancer (NSCLC) patients and prompted further studies. In the phase III JUNIPER study, previously chemotherapy treated patients with advanced stage NSCLC patients with KRAS mutations showed improved response rates and progression-free survival, which supports further investigations [74]. The MONARCH study series enrolled patients with hormone receptor positive, ErbB2-negative advanced breast cancer and led to FDA approval of abemaciclib as initial endocrine-based therapy in combination with an aromatase inhibitor [75].…”
Section: Resistance To Cdk4/6 Inhibitorsmentioning
confidence: 66%
“…The most promising results were seen in breast cancer and non-small cell lung cancer (NSCLC) patients and prompted further studies. In the phase III JUNIPER study, previously chemotherapy treated patients with advanced stage NSCLC patients with KRAS mutations showed improved response rates and progression-free survival, which supports further investigations [74]. The MONARCH study series enrolled patients with hormone receptor positive, ErbB2-negative advanced breast cancer and led to FDA approval of abemaciclib as initial endocrine-based therapy in combination with an aromatase inhibitor [75].…”
Section: Resistance To Cdk4/6 Inhibitorsmentioning
confidence: 66%
“…One identified target has been cyclin-dependent kinase (CDK) 4 [72]. In the phase III JUNIPER study (patients with KRAS-mutant NSCLC), the CDK4 inhibitor abemaciclib did not improve OS compared with erlotinib, a drug recognized to perform poorly in this setting [73]. Additionally, a recent UK study, the National Lung Matrix Trial, reported that only 1/30 patients with KRAS-mutant NSCLC showed a response to the CDK4/6 inhibitor palbociclib [74].…”
Section: A Brief History Of Kras Targetingmentioning
confidence: 99%
“…An ongoing Phase III clinical trial (JUNIPER) is evaluating the efficacy and safety of abemaciclib compared to erlotinib in previously treated patients with advanced KRAS -mutated NSCLC. The study did not meet its primary endpoint of OS but demonstrated an improvement in PFS and ORR [ 84 ].…”
Section: Krasmentioning
confidence: 99%